The State Responsibility for Identity Errors in the Issuance of Land Ownership Certificates in Judicial Proceedings - Kurniawan, Stanley; Rahayu, Mella Ismelina Farma (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This study examines the state’s responsibility for identity errors in the issuance of land ownership certificates and their implications in judicial proof. The ideal framework of Indonesian land law, as stipulated in the 1960 Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997, promises legal certainty through land certificates as strong evidence of ownership. In practice, however, administrative identity errors such as incorrect names, boundaries, or measurement data often weaken the evidentiary value of certificates in court. Using a normative juridical method based on doctrinal analysis, regulations, and court decisions, this study finds that defective certificates may be annulled even when held by good-faith owners. This highlights a research gap: the lack of systematic analysis on the state’s responsibility for administrative errors in certificates. The study concludes that the state must be accountable through preventive responsibility (error prevention), curative responsibility (administrative correction and compensation), and repressive responsibility (provision of damages). The study recommends integrating land registration with civil registry data, improving identity verification mechanisms, and strengthening legal protection to ensure land certificates effectively function as instruments of legal certainty.